Adopting Automated Essay Scoring Feedback In Malaysia: A Review Of The Literature - Ng, Sing Yii; Bong, Chih How; Lee, Nung Kion; Hong, Kian Sam (2015)
Assessing essays and providing feedback to learners is undoubtedly a daunting, time consuming task for language teachers especially for formative assessment. Formative assessment requires feedbacks that indicate learning gaps that inform ideas for further improvement. Although providing high quality feedback is important, teachers are often in dilemma to beat the deadline and hold accountable to huge class size despite the need for iterative and frequent practice. The laboriousness of essay marking often limits the occurrence of essay writing in classroom. A possible solution is to make use of an Automated Essay Scorer (AES) system that could score and generate feedback immediately. The purpose of this paper is to review on the importance of feedback and the feasibility of adopting an automated mechanism to help Malaysian English teachers to mark essays and provide feedbacks instantly. Features of good feedback, commercially available AES, reasons in favour of automated feedback based on the Malaysian context and some limitations of the system are examined. Our findings suggest that relevant and effective automated feedback mechanism can be possible through home-grown AES supplemented with properly phrased feedbacks. It can lead to self-regulated learning that empowers them for sustainable development. It is a laborious but attainable task with the cooperation and supports all parties. Hence, introducing Automated Essay Scoring Feedback (AESF), a home-grown AES is a feasible and highly anticipated tool for the Malaysian classroom.